GENETIC BIOLOGICAL PROGNOSTIC MARKERS OF COLORECTAL CANCER - Голотюк, В. В.; Юркевич, Є. М.; Голотюк, В. І.; Семенів, П. М.; Ткачук, Ю. Б.; Гончар, В. Г. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The question of cancer treatment individualization, which is based on the definition of the molecular-biological characteristics of the cancer disease is topical today. This article reviews current literature data on the possible prognostic significance of key molecular markers of colorectal cancer progression in relation to the pathogenesis of the disease.